2016
DOI: 10.1021/acsnano.6b02865
|View full text |Cite
|
Sign up to set email alerts
|

Charge Transfer States in Dilute Donor–Acceptor Blend Organic Heterojunctions

Abstract: We study the charge transfer (CT) states in small-molecule blend heterojunctions comprising the nonpolar donor, tetraphenyldibenzoperiflanthene (DBP), and the acceptor, C70, using electroluminescence and steady-state and time-resolved photoluminescence spectroscopy along with density functional theory calculations. We find that the CT exciton energy blue shifts as the C70 concentration in the blend is either decreased or increased away from 50 vol %. At 20 K, the increase in CT state lifetime is correlated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
81
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 51 publications
(92 citation statements)
references
References 27 publications
11
81
0
Order By: Relevance
“…Electron trapping likely occurs at surface defects due to Zn interstitials and oxygen vacancies, whose energies are reported to lie 0.2 -0.8 eV below the ZnO conduction band edge 19 . We note that the EL spectra peak position, and its width and intensity is dependent on ZnO processing conditions, and as noted above, that spectral peak dependence on voltage and temperature are not found in organic HJ spectra 25,26 . These observations support the conclusion that ZnO surface trap states dominate the behavior of the EL spectra peak at this OI-…”
Section: Discussionsupporting
confidence: 70%
“…Electron trapping likely occurs at surface defects due to Zn interstitials and oxygen vacancies, whose energies are reported to lie 0.2 -0.8 eV below the ZnO conduction band edge 19 . We note that the EL spectra peak position, and its width and intensity is dependent on ZnO processing conditions, and as noted above, that spectral peak dependence on voltage and temperature are not found in organic HJ spectra 25,26 . These observations support the conclusion that ZnO surface trap states dominate the behavior of the EL spectra peak at this OI-…”
Section: Discussionsupporting
confidence: 70%
“…The EQE increases slightly with temperature, with larger increases near the edges of the absorption features at l ¼ 540 nm, 590 nm, and 700 nm. The longest wavelength corresponds to the DBP:C 70 charge transfer (CT) state absorption [24].…”
Section: Resultsmentioning
confidence: 99%
“…Take a recent example in which solar cells based on tetraphenyldibenzoperiflanthene (DBP)/C 70 showed two distinct CT features in their emission spectra. In addition, the authors found that IQE dropped off dramatically in the absorption range of the lower energy CT feature . The authors identified the peaks as originating from either ordered or disordered regions of the interface, and given this assignment, it is reasonable that both the high and low energy states are emissive since they occupy distinct volumes in space.…”
Section: Outstanding Questionsmentioning
confidence: 98%
“…In addition, the authors found that IQE dropped off dramatically in the absorption range of the lower energy CT feature . The authors identified the peaks as originating from either ordered or disordered regions of the interface, and given this assignment, it is reasonable that both the high and low energy states are emissive since they occupy distinct volumes in space. However, the authors' assignment of the higher energy DBP:C 70 CT state as the more delocalized one stands in contrast to the majority of works, which correlate a higher degree of delocalization with lowering of the CT state energy.…”
Section: Outstanding Questionsmentioning
confidence: 98%